2011
DOI: 10.1016/j.cgh.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Level of α-Fetoprotein Predicts Mortality Among Patients With Hepatitis C–Related Hepatocellular Carcinoma

Abstract: Background & Aims Hepatocellular carcinoma (HCC) can result from hepatitis C (HCV)-related liver disease and is the fastest-growing cause of cancer-related death in the United States. Alpha-fetoprotein (AFP) has been used as a prognostic factor for HCC, but the value of AFP as a prognostic factor for HCV-related HCC in the United States is unknown. We investigated whether higher levels of AFP at the time of diagnosis are associated with increased mortality of patients with HCV-related HCC. Methods In a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
2
30
2
Order By: Relevance
“…However, on multivariate analysis, only AFP (≥400 ng/ml), ALT, and TACE were independent predictors of overall survival. Another study [47] also found AFP level to be an independent predictor of mortality in hepatitis C-related HCC. Though a few recent studies [48], [49] proposed that preoperative AFP levels are not useful for predicting postoperative survival of patients with early-stage HCC, AFP is used as a biomarker of HCC diagnosis [50] and has even proven useful as a marker for predicting antitumor response after radiofrequency ablation [51] and sorafenib therapy [52].…”
Section: Discussionmentioning
confidence: 87%
“…However, on multivariate analysis, only AFP (≥400 ng/ml), ALT, and TACE were independent predictors of overall survival. Another study [47] also found AFP level to be an independent predictor of mortality in hepatitis C-related HCC. Though a few recent studies [48], [49] proposed that preoperative AFP levels are not useful for predicting postoperative survival of patients with early-stage HCC, AFP is used as a biomarker of HCC diagnosis [50] and has even proven useful as a marker for predicting antitumor response after radiofrequency ablation [51] and sorafenib therapy [52].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, high levels of serum AFP were not correlated with poorer clinical endpoints in terms of recurrence and HCC-related death even in patients with initial elevation of AFP, in contrast to a large number of reports that have claimed a benefit of serum AFP measurement before surgical resection of HCC to easily and inexpensively predict long-term prognosis. [5][6][7][8][9][10][11][12] These conclusions also followed from our analyses of recurrence and death specific to HCC using the best cutoffs of serum AFP at different time points based on the AUROC values, all of which were only about 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…1 With regard to surrogate prognosis, previous studies have shown that higher serum AFP at diagnosis is associated with worse survival outcome irrespective of liver disease etiology, ethnicity, and subsequent treatment modality including surgical resection, so that AFP has been incorporated into several staging and prognostic staging systems for HCC. [5][6][7][8][9][10][11][12][30][31][32][33][34][35][36] On the other hand, 2 analytic studies by Toyoda and colleagues found that AFP alone did not predict patient survival after HCC treatment involving hepatectomy. 13,37 Another recent study of tumor markers for HCC also revealed that none of the individual positive tumor markers for HCC-AFP, lens culinaris agglutinin-reactive fraction of AFP (AFP-L3), and des-c-carboxy prothrombin (DCP)-were associated with an increased risk of tumor recurrence and disease-specific survival after hepatectomy, although triple positivity for these oncomarkers was a useful predictor of poor survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High alphafetoprotein levels are considered to be a risk factor for the development of HCC, and have been related to tumor size. Elevated AFP levels are also regarded as an independent predictor of HCC mortality in patients with cirrhosis due to HCV infection (27), though they are of little use in establishing an early diagnosis of the disease (28). In the present cohort, only 20% showed AFP elevation at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 54%